Style and reader response minds, media, methods - Bell, Alice, 1979-; Browse, Sam; Gibbons, Alison; Peplow, David (Linguistic approaches to literature ;, 2021)
"Style and Reader Response: Minds, media, methods profiles the diversity of theoretical and methodological approaches in reception-oriented research in stylistics. Collectively, the chapters investigate how real readers, players, audiences, and viewers respond to, experience, and interpret texts. Contributions to the book investigate discourse types such as contemporary literature, poetry, political speeches, digital fiction, art exhibitions, and online news discourse. The volume also exemplifies the variety of empirical approaches in reception research, with contributors drawing on a range of methods including discussion groups, interviews, questionnaires, and think-aloud protocols with data analysed from both online and offline sources. Style and Reader Response makes an important contribution to an emerging paradigm within stylistics in which verifiable insights from readers are used to generate new models and new understandings of texts across media, with each essay demonstrating the centrality of empirical research for theoretical, methodological, and/or analytical advancements within and beyond stylistics"--